Functionalization of bacterial microcompartment shell interior with cysteine containing peptides enhances the iron and cobalt loading capacity - Kalnins, Gints; Bertins, Maris; Viksna, Arturs; Tars, Kaspars (Biometals, 2024)
Bacterial microcompartments (BMCs) are prokaryotic organelles involved in several biochemical processes in bacterial cells. These cellular substructures consist of an icosahedral shell and an encapsulated enzymatic core. The outer shells of BMCs have been proposed as an attractive platform for the creation of novel nanomaterials, nanocages, and nanoreactors. In this study, we present a method for functionalizing recombinant GRM2-type BMC shell lumens with short cysteine-containing sequences and demonstrate that the iron and cobalt loading capacity of such modified shells is markedly increased. These results also imply that a passive flow of cobalt and iron atoms across the BMC shell could be possible.